Gender Gaps in Peru : An Overview - Muller, Miriam; Paz, Carmen de (World Bank, Washington, DC, 2019)
Closing the existing gender gaps will be required to boost shared prosperity and maximize poverty reduction efforts in Peru over the coming years. Gender inequities are not only unfair from an ethical and social perspective, but also economically inefficient. Greater gender equality can raise overall productivity, improve development outcomes, especially of the next generation, and lead to more representative decision making. This review of gender issues aims to uncover the main gender gaps in the country, and to identify potential policy recommendations that could help closing them in the coming years. Chapter 1 covers the legal and institutional framework and the issue of the agency of women; Chapter 2 provides an overview the situation with regards to the main endowments of health and education; and Chapter 3 deals with the existing gender gaps in economic opportunity.